Efektivitas Penerapan Bahan Ajar Berbasis Kearifan Lokal Pada Peserta Didik Kelas IV - Ayu Rahmawati; Berti Yolida; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the effectiveness of used of local wisdom-based teaching materials to increase the activity and learning outcomes of fourth grade students on Theme 3